Inovasi Paving Block Ramah Lingkungan dengan Memanfaatkan Limbah Geodipa Sebagai Pengganti Sebagian Semen - Fikroni; Juara, Agus; Suharto (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2023)
The increasing growth of the factory industry has created new attention to waste which needs to be managed more seriously so that it can provide benefits, especially in the construction sector. For this reason, it is necessary to conduct research on this problem. In this study, researchers conducted research using geodipa waste. The percentage of geodipa waste used in this research is 3%, 5%, 8%, 10% and 12% of the cement weight requirement using a mixture of 1PC:6Ps and 100 ml of water for 1 paving block with a mold thickness of 6 cm, width 10 cm, 20 cm long using manual tools. The test results using geodipa waste for a mixture of an average of 8% compressive strength test produced were 16.13 MPa for Rp. 1,066,-/seed according to SNI-03-0691-1996 including class C quality (can be used for pedestrians) while for the normal mixture the resulting compressive strength test was 11.33 MPa for Rp. 1,100,-/seed including class D quality (can be used for parks and other uses) From the results of the compressive strength test of the paving blocks, it can be concluded that the addition of geodipa waste produces better results.